2005
DOI: 10.1163/156854105776186325
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Meloidogyne spp. based on 18S rDNA and the intergenic region of mitochondrial DNA sequences

Abstract: Summary -The 18S rDNA of 19 populations of Meloidogyne spp. was amplified and directly sequenced. The region of mitochondrial DNA, located in the 3 portion of the gene that codes for cytochrome oxidase subunit II (COII) through a portion of the 16S rRNA (lRNA) gene, from 16 of these populations was cloned and sequenced. Heteroplasmic sequences were identified from both rDNA and mtDNA regions for several taxa. Several sequences sampled from nominal taxa differed from previously published accounts. Phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 26 publications
3
20
1
1
Order By: Relevance
“…The trees obtained from MP analysis of different rDNA sequences agreed with those obtained in Neighbour Joining and MP analysis by Castillo et al (2003), Landa et al (2008), Palomares Rius et al (2007, and Tigano et al (2005). The addition of the sequences of this new species or additional sequences from the GenBank database to the maximum parsimony analyses caused small subtle changes in topology of the dendrograms shown in Fig.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The trees obtained from MP analysis of different rDNA sequences agreed with those obtained in Neighbour Joining and MP analysis by Castillo et al (2003), Landa et al (2008), Palomares Rius et al (2007, and Tigano et al (2005). The addition of the sequences of this new species or additional sequences from the GenBank database to the maximum parsimony analyses caused small subtle changes in topology of the dendrograms shown in Fig.…”
Section: Discussionsupporting
confidence: 83%
“…The addition of the sequences of this new species or additional sequences from the GenBank database to the maximum parsimony analyses caused small subtle changes in topology of the dendrograms shown in Fig. 6 compared to that reported previously (Castillo et al, 2003;Tigano et al, 2005). MP analysis showed that the 18S, ITS1-5·8S-ITS2 and D2-D3 sequences of M. silvestris n. sp.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Enquanto, para a amplificação da região do mtDNA foram utilizados os primers C2F3 (5´-GGTCAATGTTCAGAAATTTGTGG-3`) e 1108 (5`-TACCTTTGACCAATCACGCT-3`) (Powers & Harris, 1993 Esses marcadores permitiram a diferenciação de M. mayaguensis com relação a outras espécies comuns de Meloidogyne devido ao tamanho do produto de amplificação. Os resultados obtidos confirmaram a detecção de M. mayaguensis nas duas propriedades, pois os fragmentos de PCR obtidos foram os mesmos previamente descritos para essa espécie, isto é 780 pb para IGS (Block et al, 1997;Adam et al, 2007) e 705 pb para a região do DNA mitocondrial (Block et al, 2002;Brito et al, 2004;Tigano et al, 2005;Jeyaprakash et al, 2006) …”
unclassified
“…This cluster was successfully separated on the basis of AFLP and RAPD data, suggesting that these three isolates may belong to the same, as yet undescribed, species. The same unidentified RKN have been compared to several of the most common species of Meloidogyne in a phylogenetic study based on mitochondrial DNA sequences, and were shown to be closely related (c. 85% bootstrap value) to isolates that have since been confirmed as M. inornata (Carneiro et al, 2008b) and M. ethiopica (Tigano et al, 2005). However, the SCAR marker developed here for M. ethiopica did not result in any PCR amplification for this Meloidogyne sp.…”
Section: Discussionmentioning
confidence: 89%